CRISPR-based genome editing in primary human pancreatic islet cells - Romina J. Bevacqua (Nature Portfolio, 2021)
The editing of primary human islets could provide insight into diabetes pathogenesis. Here the authors use CRISPR-Cas9 to target regulatory elements associated with T2D susceptibility.